Analysis of degradation mechanisms in AlInN/GaN HEMTs by electroluminescence technique. (January 2017) - Berthet, F.; Petitdidier, S.; Guhel, Y.; Trolet, J.L.; Mary, P.; Vivier, A.; Gaquière, C.; Boudart, B.
Highlights: AlInN/GaN transistors have a strong interest for high power electronic. AlInN/GaN transistors has a strong interest for high temperature applications. Pre-existent electrical traps effects have an influence on the reliability of AlInN/GaN HEMTs. Degradation of the IDS and Raccess has been highlighted during electrical stresses. Degradation mechanisms in GaN-based transistors are studied by electroluminescence techniques. Abstract: In this paper, the impact of a severe on-state stress on the IDS (VDS, VGS ) characteristics of AlInN/GaN devices is analyzed by electroluminescence technique performed at room temperature. In fact, the devices operate in bias conditions that allow measuring the bell- shaped gate current. To our knowledge, it is the first time that a bell-shaped gate current centered at a positive VGS and measured at room temperature has been shown for an AlInN/GaN transistor. We have also highlighted that electroluminescence spectra are related to the superposition of intraband radiative electron transitions, Fabry-Perot oscillations, and emission bands induced by recombination of electrons due to electron traps. In these conditions, it is not so easy to extract energies levels of electron traps existing in unstressed and stressed AlInN/GaN HEMTs from electroluminescence spectra. Thus, we have also shown that the electrical degradations induced by on-state stress are mainly related to the trapping of hot electron by deep pre-existing electron traps in the devices. Moreover, we have highlighted the existence of two electron traps activated at 1.6 and 1.8 eV in the devices.